The therapeutic potential of Rosiglitazone in modulating scar formation through PPAR-γ pathway - Fang, Qing-qing; Gu, Yang-jun; Wang, Yong; Wang, Zheng-cai; Lin, Xiao-ying; Guo, Kai; Zhuang, Ze-ming; Zhong, Xin-cao; Zhang, Li-yun; Chen, Jian; Tan, Wei-qiang (European journal of pharmacology, 2025)
The prevention and treatment of scars has always posed a challenge in the medical field. Researchers have reached the consensus that safe, effective and affordable treatments are needed. Here, by conducting non-targeted metabolomics and RNA sequencing experiments, we revealed that a significant number of metabolites and genes related to glucose and lipid metabolism underwent changes during scar formation, with peroxisome proliferator-activated receptor-γ (PPAR-γ) exerting a profound influence. Considering that rosiglitazone is a selective orally active PPAR-γ receptor agonist, scar models were induced in rats, and rosiglitazone was administered at different dosages. We characterized rosiglitazone as a crucial mediator in a rat scar model in vivo and in vitro in two models of transforming growth factor β1(TGF-β1) stimulated fibroblasts (NIH 3T3 and 3T3 L1). Functionally, activation of PPAR-γ with rosiglitazone effectively impedes fibrosis and mitigates scar formation. Rosiglitazone also inhibits some inflammatory factors, and downregulates triglyceride, lactic acid, glycogen and lactic dehydrogenase levels in rat scars. Conversely, rosiglitazone increases adenosine triphosphate (ATP) production and increases free fatty acid levels and the activity of acetyl-CoA carboxylase, fatty acid synthetase, succinate dehydrogenase. Collectively, these findings shed light on the underlying mechanisms and suggest that the use of rosiglitazone could be a promising therapeutic approach to alleviate fibrosis and reduce scar formation. [Display omitted] •Scar formation is an annoying outcome of all kinds of deep trauma.•Altered glucose and lipid metabolism were observed during scar formation.•Down-expression of PPAR-γ was crucial to the fibrotic effect of cells and rats.•Activating PPAR-γ by rosiglitazone can protect against severe scar formation.